Percutaneous coronary intervention in left main coronary artery disease with or without intravascular ultrasound: A meta-analysis - Ye, Yicong; Yang, Ming; Zhang, Shuyang; Zeng, Yong (PloS one, 2017)
This meta-analysis compared IVUS-guided with angiography-guided PCI to determine the effect of IVUS on the mortality in patients with LM CAD. Current guidelines recommend intravascular ultrasound (IVUS)-guided percutaneous coronary intervention (PCI) in patients with left main coronary artery disease (LM CAD; Class IIa, level of evidence B). A systematic search of the MEDLINE, Embase, and Cochrane Central Register of Controlled Trials databases was conducted to identify randomized or non-randomized studies comparing IVUS-guided PCI with angiography-guided PCI in LM CAD. Ten studies (9 non-randomized and 1 randomized) with 6,480 patients were included. The primary outcome was mortality including all-cause death and cardiac death. Compared with angiography-guide PCI, IVUS-guided PCI was associated with significantly lower risks of all-cause death (risk ratio [RR] 0.60, 95% confidence interval [CI] 0.47-0.75, p<0.001), cardiac death (RR 0.47, 95% CI 0.33-0.66, p<0.001), target lesion revascularization (RR 0.43, 95% CI 0.25-0.73, p = 0.002), and in-stent thrombosis (RR 0.28, 95% CI 0.12-0.67, p = 0.004). Subgroup analyses indicated the beneficial effect of IVUS-guide PCI was consistent across different types of studies (unadjusted non-randomized studies, propensity score-matched non-randomized studies, or randomized trial), study populations (Asian versus non-Asian), and lengths of follow-up (<3 years versus ≥3 years). IVUS-guided PCI in LM CAD significantly reduced the risks of all-cause death by ~40% compared with conventional angiography-guided PCI. PROSPERO registration number: CRD 42017055134.